El Derecho Internacional Público y el Derecho Nacional - Romero-Pérez, Jorge Enrique (2013)
The Convention of Vienna of the Treaties, of 1969, codes the Common Law in this matter, establishing the supremacy of the International Law on the National Law, including the Political Constitutions.